Full solid-phase total synthesis of macrocyclic natural peptides using four-dimensionally orthogonal protective groups. Issue 27 (24th June 2019) - Itoh, Hiroaki; Inoue, Masayuki
Abstract : This review focuses on four-dimensionally orthogonal protective group strategies for the full solid-phase synthesis of macrocyclic natural peptides. Abstract : Fmoc-based solid-phase synthesis provides efficient access to both linear and macrocyclic peptides. To synthesize complex macrocyclic polyamides using Fmoc chemistry, multiple protective groups with orthogonal reactivities are generally employed because the free amines and carboxylic acids of specific residues must be selectively exposed prior to amide formation. This review focuses on four-dimensionally orthogonal protective group strategies for the full solid-phase synthesis of macrocyclic peptides with branched chains (polymyxin E2 and daptomycin) and a tricyclic natural peptide (lacticin 481).